Comparison of the upper respiratory tract width at the level of the adenoid in patients with normal and abnormal breathing route - Duda, Anna; Stós, Wojciech (Forum Ortodontyczne / Orthodontic Forum, 2018)
This study assesses the upper respiratory tract width at the level of the adenoid in patients with a normal (nasal) and abnormal (oral or mixed) breathing route. Aim. To compare the upper respiratory tract width in the study group (abnormal breathing route) and control group (normal breathing route) and to determine the cut-off point and mean limit values in order to conduct a differential diagnosis between a habitual and constitutional breathing route. Material and methods. The study included 221 patients treated at the Aquadent-Ortoestetyka Clinic in Kielce. Based on the medical history taken, clinical examination and subjective evaluation of the upper respiratory tract width according to Holmberg 112 patients were enrolled into the study group and 109 patients into the control group. The upper respiratory tract width was measured with two different linear methods: a modified method by Holmberg and Linder-Aronson, and the Linder-Aronson and Henricson method (AD1-PNS, AD2-PNS). Results. In the study group the mean value of the Holmberg measurement is 4.25 mm, and in the control group – 14.1 mm. Mean values of AD1- PNS and AD2-PNS measurements in the study group are 8.1 mm and 9.5 mm, respectively, and they can be regarded as mean limit values. The 6 mm Holmberg measurement is the cut-off value between the study and control groups, and it should be monitored. In relation to the Holmberg measurement a difference between the study and control groups is 9.85 mm. Regarding AD1-PNS and AD2-PNS measurements a difference between the study and control groups is 11.4 mm and 10.0 mm, respectively. Conclusions. The upper respiratory tract width at the level of the adenoid shows a statistically significant difference between the study and control groups. It may indicate significant narrowing of the upper respiratory tract at the level of the adenoid in the study group or a different type of morphology of the facial skeleton. Limit values obtained in the study allow differentiation of a habitual and constitutional breathing route. (Duda A, Stós W. Comparison of the upper respiratory tract width at the level of the adenoid in patients with normal and abnormal breathing route. Orthod Forum 2018; 14: 106-18).